PENGARUH PENGGUNAAN PLATFORM GENIALLY TERHADAP HASIL BELAJAR SISWA PADA MATERI EKOSISTEM MATA PELAJARAN IPAS KELAS 3 DI SD INPRES OSMOK - julitha bessie; Jannes Bastian Selly; Rista Apriliya Devi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of using the Genially platform on student learning outcomes in the ecosystem topic of IPAS subject for third-grade students at SD Inpres Osmok. The research was motivated by low student achievement due to conventional teaching methods and limited use of interactive media. This study employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The subjects were 25 students from class III B. Data collection techniques included observation, documentation, and multiple-choice tests, while data were analyzed using normality, homogeneity, and paired sample t-test through SPSS version 27. The results showed a significant increase in the average score from a pretest score of 51.12 to a posttest score of 72.80. The t-test revealed a significance value of 0.000 < 0.05, indicating a positive impact of Genially on student learning outcomes. Additionally, observation scores of 83 (teacher) and 82 (students) reflected very good implementation. In conclusion, the use of Genially proved effective in enhancing student learning outcomes and fostering a more interactive and meaningful learning experience.